Reshaping Governance Mechanisms in Social and Solidarity Economy Organizations: A Strategic Management Perspective from the Moroccan Context - Mohammed OUDRHIRI SAFIANI; Youssef AZIZI; EL HIRI Abderrazak (International Journal of Scientific Research and Innovative Studies, 2025)
Moroccan Social and Solidarity Economy (SSE) organizations operate at the intersection of participatory norms and performance-driven expectations, confronting governance challenges rarely captured in Global-North scholarship. Adopting an abductive, multiple-case design, this study investigates how six SSE entities—cooperatives, mutual-benefit associations, and social enterprises—translate institutional plurality into strategic effectiveness. Documentary analysis, thirty semi-structured interviews, and non-participant observation reveal a tripartite governance typology: consensus-anchored models that prioritise egalitarian deliberation yet suffer protracted decision cycles; hybrid-modular structures that superimpose task-specific committees and balanced-scorecard dashboards onto member assemblies; and managerialised configurations dominated by competency-based boards and real-time KPI monitoring. Hybrid-modular organizations achieve superior ambidexterity, coupling democratic participation with formal controls to diversify revenue streams, accelerate decision latency, and enhance stakeholder legitimacy. Three recurring tensions—regulatory ambiguity versus standardisation, social-impact fidelity versus revenue pursuit, and territorial legitimacy versus scalability—act as generative forces when addressed through iterative “logic-bricolage” routines such as layered formalisation, temporal sequencing, and boundary realignment. The findings reframe governance as a path-dependent capability that orchestrates micro-level structural tweaks into macro-level resilience, extending hybrid-organization theory into contexts shaped by Islamic-finance proximity and state-led performance agendas. Practically, the study recommends governance-maturity roadmaps for managers and incentive schemes that reward incremental formalisation for policymakers. Future research should employ longitudinal and mixed-method designs to test the transferability of the logic-bricolage model across MENA ecosystems. Keywords : governance hybridity ; strategic ambidexterity ; Social and Solidarity Economy ; dynamic capabilities ; institutional logics ; Morocco ; logic bricolage. Received Date: July 19, 2025 Accepted Date: August 11, 2025 Published Date: August 30, 2025 Available Online at https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/424